Analysis of the implementation complexity of the cryptosystem on the Suzuki group - Khalimov, G.Z.; Kotukh, Y.V.; Sergiychuk, Yu.A.; Marukhnenko, A.S. (Radiotekhnika, 2018)
Implementations for cryptosystems of finite groups based on logarithmic signature and covering are considered. A logarithmic signature is exemplified by a permutation group with the asymmetry of encryption and decryption algorithms. Description of the improved cryptosystem MST3 in Suzuki 2-group with the order of the group q2 is given. The Suzuki 2-group use has a significant advantage in implementation, due to the large center and simple group operation. Cost estimates for encryption, decryption and comparison with the RSA algorithm are obtained.